Genome-Wide Analysis of the G2-Like Transcription Factor Genes and Their Expression in Different Senescence Stages of Tobacco (Nicotiana tabacum L.) - Qin, Mingyue; Zhang, Binghui; Gu, Gang; Yuan, Jiazheng; Yang, Xuanshong; Yang, Jiahan; Xie, Xiaofang (Frontiers in Genetics, 2021)
The G2-like transcription factors (GLK) play important roles in regulating chloroplast growth, development and senescence in plant. In this study, a total of 89 NtGLK genes (NtGLK1-NtGLK89) were identified in the tobacco genome and were classified into 10 subfamilies with variable number of exons and similar structure organizations based on the gene structures and protein motif analysis. Twelve segmental duplication pairs of NtGLK genes were identified in the genome. These NtGLK genes contain two conserved helix regions related to the HLH structure, and the sequences of first helix region are less conserved than that of the second helix motif. Cis-regulatory elements of the NtGLK promoters were involved in light-responsiveness, hormone treatment, and physiological stress widely. Moreover, a total of 206 GLK genes from tomato, tobacco, maize, rice and Arabidopsis were retrieved and clustered into 8 subgroups. Our gene expression analysis indicated that the members of NtGLKs showed differential expression pattern in tobacco leaves at five senescence stages. The expression levels of six NtGLK genes in group C were reduced coincided precisely with the increment of the degree of senescence which might be associated with the function of leaf senescence of tobacco. Our results have revealed valuable information for further functional characterization of the GLK gene family in tobacco.